2001
DOI: 10.1034/j.1600-0420.2001.079002169.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of electrophysiology results in patients with epilepsy and vigabatrin associated visual field loss

Abstract: ABSTRACT.Purpose: To determine the value of electrophysiological findings in patients with temporal lobe epilepsy and to relate these findings to the amount of concentric contraction of the visual field and the use of vigabatrin. Methods: Electro-retinograms and electro-oculograms were done on 30 patients, operated for temporal lobe epilepsy. The patients were divided into three groups: (A) concentric contraction of the visual field associated with a history of vigabatrin medication (15 patients), (B) normal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Several theories have been proposed about the cause of vigabatrin-associated VFDs. 12 These include toxic reaction (treatment duration and cumulative dosage, 5 daily dose 13 ), idiosyncratic reaction, 14 polypharmacy, 15 pharmacogenetic difference, 14 elevated levels of retinal ornithine, 16 light exposure, taurine deficiency, 17 GABA accumulation in the retina, 18 dysfunction in GABA-innervated horizontal and amacrine cells in the inner plexiform layer of the retina, 10 and the infantile spasm itself. 19 Maximum daily dose was a single most reliable indicator of risk of VFDs in VBG-exposed patients in one study.…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have been proposed about the cause of vigabatrin-associated VFDs. 12 These include toxic reaction (treatment duration and cumulative dosage, 5 daily dose 13 ), idiosyncratic reaction, 14 polypharmacy, 15 pharmacogenetic difference, 14 elevated levels of retinal ornithine, 16 light exposure, taurine deficiency, 17 GABA accumulation in the retina, 18 dysfunction in GABA-innervated horizontal and amacrine cells in the inner plexiform layer of the retina, 10 and the infantile spasm itself. 19 Maximum daily dose was a single most reliable indicator of risk of VFDs in VBG-exposed patients in one study.…”
Section: Discussionmentioning
confidence: 99%
“…Electroretinograms were recorded after 15 min preadaptation (waiting room FL tubes). Further details have been described previously (Hardus et al 2001b). The examinations were performed by two technical assistants, alternately.…”
Section: Electrophysiologymentioning
confidence: 99%
“…In a former study, we found abnormalities in the electro-oculogram (EOG) and electroretinogram (ERG) single flash, mainly in the b-wave, scotopic and photopic, in approximately 50% of subjects with VGB-VFL (Hardus et al 2001b). Decreased photopic b-wave amplitude was found with more extensive visual field loss.…”
Section: Introductionmentioning
confidence: 98%
“…In many studies of the effect of vigabatrin in patients there was a reduction of the b-wave in parts of the patients, but not in all [3,4,8,9,26,42,50]. In some instances, the rod b-wave was not statistically different from those of control subjects [8,53].…”
Section: Multiple Gabaergic Influences On the B-wavementioning
confidence: 97%
“…The multiple GABAergic influences on the generation of the b-wave may also explain why, during vigabatrin therapy, which can impair peripheral vision, there are no consistent changes of the b-wave [4,8,24,26], although the oscillatory potentials and the 30-Hz flicker amplitude of the ERG seem to correlate with visual field loss [4,23,24,25,42]. When given therapeutically, vigabatrin is taken up by amacrine cells and blocks their normal metabolism.…”
Section: Multiple Gabaergic Influences On the B-wavementioning
confidence: 99%